ANALISIS HISTOLOGIS LAMUN Halodule uninervis dan Cymodocea serrulata YANG YANG BERASAL DARI PERAIRAN TERCEMAR LOGAM BERAT TIMBAL (Pb) DI KEPULAUAN BANGKA - Francischa Aprilya; Farikhah Farikhah; Andi Rahmad Rahim; Dwi Rosalina (Universitas Muhammadiyah Gresik, 2020)
Bangka Islands is a coastal area which has many coastal activities such as tin mining activities, ports/docks boatand ship transportation and residential areas. This can provide pollutant input into the water. Seagrass Halodule uninervis and seagrass Cymodocea serrulata is a flowering plant that live in the sea have extensive deployment in the waters of Bangka. One of the marine plants that can be used as a bioindicator of water pollution is seagrass. Seagrass is in the water column and the body parts interact directly with the water. This research was conducted from December 2019 to January 2020. The research sites were in the Laboratory of Muhammadiyah Gresik University and the Laboratory of Pathology, Anatomical Faculty of Medicine, University of Brawijaya Malang. The purpose of this study was to study the anatomical changes in root tissue, rhizome and leaves of Halodule uninervis seagrass andseagrass Cymodocea serrulata in response to contamination of heavy metal lead (Pb). This research was conducted in a descriptive qualitative manner with 3 body parts: roots, rhizome and leaves. The results of this study indicated that the epidermal,cells cortex and endodermalin the roots were thickened. Cell wall thickening occurs in the epidermis Rhizome. Likewise in the leaves, the phloem occurs thickening. In general, changes in the anatomical features of roots, rhizomes, and leaves were observed in response to an increase in lead concentration. The results showed that Halodule uninervis seagrass andseagrass Cymodocea serrulata developed several levels of tolerance to heavy metals, especially lead (Pb).